The Pedagogic Competence of Non-Graduate Special Education Teachers : A Study of Instructional Supervision in Special Education School - Darmawan, Luqi; Hermanto, Hermanto; Putera, Agustian Ramadana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to analyze the implementation of instructional supervision in developing the pedagogic competence of non-graduate special education class teachers at SLB YKK Pacitan dan SLB Negeri Ngadirojo. This study used a qualitative approach with a case study method. The data were obtained through interviews, observation, and study documentation. The validity of the data in this study had criteria for credibility and confirmability. Analysis of the data used was data collection, data condensation, data display, and conclusion drawing/verification. The results of this study showed that; 1) The planning stage of instructional supervision by forming a supervision team, analyzing the previous year’s learning supervision, and compiling a learning supervision program. 2) Implementation of instructional supervision using individual techniques and collaborative approaches. 3) Follow-up instructional supervision by guiding using learning media, understanding various characteristics of children with special needs, guiding teachers in using sign language and reading braille, and involving teachers in various training and workshops.